On-farm research manual : (Department of Agriculture, Bureau of Agricultural Research, 1990)
The book gives an overview and directions of agricultural research. It also discusses on farming systems approach, organizing multidisciplinary teams; feedback mechanism; cropping systems research; crop-livestock systems; fisheries and pilot production programs